Comprehensive Non-Pharmacological Management of Rheumatoid Arthritis: A Multidisciplinary Approach - Możdżan, Zofia; Majtas, Adrian; Gronek, Konrad; Zheng, Edward; Olejnik, Agnieszka; Tambor, Jakub; Polak, Mateusz; Tambor, Igor; Błasiak, Aleksandra; Biskup, Laura (Quality in Sport, 2026)
Background. Rheumatoid arthritis (RA) is a chronic autoimmune disease that leads to joint destruction, chronic pain, and significant functional impairment. While pharmacological treatment remains the cornerstone of therapy, it is increasingly recognized that optimal patient outcomes require a holistic approach. Non-pharmacological interventions are essential to address the physical, psychological, and social challenges faced by patients. Aim. The aim of this study is to evaluate the effectiveness of various non-pharmacological strategies in the management of RA and to highlight the importance of a coordinated, multidisciplinary team in improving patient quality of life and functional status. Material and methods. A comprehensive review of current clinical guidelines and recent literature (from databases such as PubMed and Scopus) was conducted. The analysis focused on interventions including physical therapy, occupational therapy, nutritional counseling, psychological support, and patient education programs within a multidisciplinary framework. Results. The findings indicate that regular aerobic and resistance exercise, combined with joint protection techniques, significantly reduce pain and fatigue while improving joint mobility. Dietary interventions (e.g., Mediterranean diet) and psychological interventions (e.g., Cognitive Behavioral Therapy) contribute to better disease control and mental well-being. A multidisciplinary approach, involving rheumatologists, physiotherapists, dietitians, and psychologists, leads to higher treatment adherence and better functional outcomes compared to monodisciplinary care. Conclusions. Non-pharmacological management is a vital component of RA care that complements medical treatment. A well-structured, multidisciplinary approach ensures personalized care, targets diverse symptoms, and empowers patients to manage their condition effectively, ultimately leading to a better quality of life.